Pharmacokinetics of Local Anesthetics in Dentistry: The Example of Articaine-Containing and Mepivacaine- Containing Anesthetics - A. Machin; S. A. Fokina; T. A. Mityushkina; K. Yu. Filippov; E. K. Korovushkina (Эндодонтия Today)
Aim. To analyze current data on the pharmacokinetics of drugs used for local anesthesia in dental practice, with particular emphasis on articaine-containing and mepivacaine-containing anesthetics.   Materials and Methods. The study of up-to-date information from the Cyberleninka, Elibrary, Google Scholar and PubMed electronic databases was carried out during a systematic review of the literature. Selected and included articles, the content of which concerns the pharmacokinetics of local anesthetics articaine and mepivacaine.   Results. 55 publications were reviewed. After analyzing the literature for inclusion criteria, the total number of publications has become 42.   Conclusions. According to the analyzed data, the choice of local anaesthetic solution should be made individually for each patient and be based on the pharmacokinetics of the drug.